Assessing Customer Satisfaction in Relation to Service Quality at PLN in Cimahi City - Aldi Aryaman; Ani Surtiani; Warman Suryaman (Innovation Business Management and Accounting Journal, 2024)
The purpose of this study is to determine the effect of service quality on PLN customer satisfaction at PT. Haleyora Powerindo Cimahi Kota. This research method uses a quantitative approach to the survey method. The population in this study is the average monthly PLN customer at PT. Haleyora Powerindo Cimahi City, namely 652 customers. Questionnaires using a Likert scale were distributed to a sample of 87 customers determined by the Slovin formula (error rate of 10%). As for statistical data analysis using simple linear regression analysis by testing the t test. The results of the study concluded that Service Quality affects PLN Customer Satisfaction at PT. Haleyora Powerindo Cimahi Kota. The magnitude of the contribution of service quality to PLN customer satisfaction at PT. Haleyora Powerindo Cimahi Kota amounted to 61.6% while the remaining 38.4% was influenced by other factors not examined in this study. This study highlights the crucial role of service quality in customer satisfaction at PT. Haleyora Powerindo Cimahi Kota, underscoring the need for focused improvements in this area to significantly enhance overall customer experience.